Detection of Mycoplasma gallisepticum and Mycoplasma synoviae among Commercial Poultry in Khouzestan Province, Iran - R. Ghadimipour; D. Gharibi; M. Mayahi (Archives of Razi Institute, 2018)
Mycoplasmas are important  avian  pathogens,  which  can  cause  both  respiratory  disease  and  synovitis  in  poultry  that  result  in  considerable  economic  losses  to  the  poultry  industry  all  over  the  world.  The  aim  of  this  study  was  to  determine  the  prevalence  of  Mycoplasma  gallisepticum  and  Mycoplasma  synoviae  infections  among  commercial  poultry  flocks  in  Khouzestan  province,  Iran,  using  the  polymerase  chain  reaction  (PCR)  technique. Totally,  290  tracheal  swab  samples  were  collected  from  19  broiler  flocks  and  4  layer-breeder  flocks,  with or  without  respiratory  signs,  in  different  areas  of  Khouzestan  province  within  six  months.  The  PCR  tests  were  applied  for  the  specific  amplification  of  16S  rRNA  (185  bp)  and  vlhA  (392  bp)  genes.  Out  of  100  swab  samples  obtained  from  the  layer-breeder  flocks,  1  and  72  specimens  were  positive  for  M.  gallisepticum and M.  synoviae, respectively.  In  this  regard,  out  of  the  4  layer-breeder  flocks,  1  (25%)  and  4  (100%)  flocks  were  positive  for  M.  gallisepticum and  M.  synoviae,  respectively.  However, none of the studied broiler flocks were M.  gallisepticum- or  M.  synoviae-positive.  According  to  the  results,  the  PCR  technique  could  be  concluded  as  a  rapid  method  for  the  accurate  identification  of  M.  gallisepticum and  M.  synoviae infections  in  commercial  poultry  flocks.  The results were indicative of the low prevalence of M.  gallisepticum in  the  studied  flocks  in  Khouzestan  province.  On the other hand, M.  synoviae  was  widely  distributed  among  layer-breeder  flocks  in  this  province.